Rising powers and global governance : changes and challenges for the world's nations - Burki, Shahid Javed (Palgrave Macmillan, 2020)
Contents: 1.Global Change and its Consequences2. A Receding America?3. Rising China4. Rising India5. Russia: A Revanchist State6. The Afghan Conundrum7. Iran's Reentry into the World8. The Rise of Extremist Islam9. Europe under Stress10. Demographic Changes11. Trade: A Major Driver of Global Growth and Integration12. Climate Change and its Consequences13. Technology and Development14. The Final Word: Broken Countries and Breaking Systems.